Hungarian Monitoring, 16 February 1989 . [Magyar rádiófigyelő], 1989. február 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - US continues arms transports to Afghan rebels - Perestroika gets stalls due to lack of economic successes - On the Polish strike movement - Forceful measures against opposition in Czechoslovakia - On the Afghan president's Moscow press conference Domestic Affairs: - Miklós Németh's speech at the Cable Works - Imre Pozsgay talks to UK paper "The Independent" on possibilities for compromise between Hungarian Socialist Workers' Party (MSZMP) and independent parties - Károly Grósz's account of domestic situation reassures Prague leaders - Still no decision on exhumation of Imre Nagy and colleagues, says secretary of state for justice - Smallholders Party: backsliding, halting process of democratization must not be allowed - Editors dismissed from "Tiszatáj" magazine rehabilitated - Hungarian parliamentary delegation in discussions in Strasbourg Külpolitika: - Az Egyesült Államok folytatja fegyverszállításait az afgán felkelőknek - A gazdasági sikerek hiányában elakad a peresztrojka - A lengyelországi sztrájkmozgalomról - Erélyes intézkedések Csehszlovákiában az ellenzékkel szemben - Az afgán alelnök moszkvai sajtóértekezletéről Belpolitika: - Németh Miklós beszéde a Kábelművekben - Pozsgay Imre az Independent c. angol lapnak nyilatkozott az MSZMP és a független pártok között létrejövő kompromisszum lehetőségéről - Grósz Károlynak az ország belső helyzetéről adott beszámolója megnyugtatta a prágai vezetőket - Még mindig nem döntöttek Nagy Imre és társai holttestének exhumálásáról, közölte az igazságügyi államtitkár - A kisgazdapárt szerint, nem szabad megengedni a visszarendeződést, a demokratizálási folyamat megállítását - Rehabilitálják a TISZATÁJ elbocsátott szerkesztőit - Magyar parlamenti delegáció tárgyal Strasbourgban